Class Bias in Indonesian’s post-reformation film revival - Ade Armando,; Nina Mutmainnah,; Hendar Putranto, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper describes how the Indonesian film industry has experienced a revival to counter Hollywood dominance since the beginning of the Reformation Era in the 2000s. However, conditions that hinder the growth of the Indonesian film industry are mainly due to the concentration of movie theatres and film screens in big cities. Indonesian films are predominantly consumed by groups from the upper socioeconomic levels and ignored by the middle and lower economic strata. This article seeks to portray whether the movement against Hollywood dominance would be effective if Indonesian films were only directed at this particular audience segment. To analyse the development of the Indonesian film industry in the post-reformation era (2000-current), the authors used a nationwide survey from Saiful Mujani Research and Consulting, conducted from August 31 to September 9, 2019, shortly before the COVID-19 Pandemic hit globally. To corroborate the survey's findings, the authors also distributed a closed questionnaire to 100 students at Undergraduate Program in Communication, Universitas Indonesia, and followed this with in-depth interviews with several students. The authors seek to study the revival of Indonesian films despite the decade-long dominance of Hollywood films and, recently, South Korean films. The research question proposed in this paper is: Can Indonesia break away from Hollywood's dominance? For this reason, this research focuses on the availability and modality of Indonesian market-targeted millennial and post-millennial film audiences to support the revival of the national film industry to compete with the dominance of Hollywood films.